EPISTEMOLOGI LOGIKA MATEMATIKA MENURUT WITTGENSTEIN - , Hardi Suyitno, Drs.,Mpd. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The dissertation entitled \"Epistemology of Logical Mathematics According to Wittgenstein\" aims at revealing and describing Wittgenstein's conception of epistemology of mathematical logic which covers the relationship between language and the world's reality, the relationship between mathematics and language, the relationship between mathematical logic and mathematics, as well as the nature of truth of mathematical logic and its relevance to the development of mathematics education. The results of the research are 'expected to be beneficial to the development of new discourses on the studies in philosophy of mathematical logic, to the advancement of science, as well as to the development of mathematics education in Indonesia. The research employs mathematical logic as its material object and epistemology as its formal object. Primary sources of the research are Tractatus Logico-Philosophicus, Philosophical Investigations, and Remarks on Philosophy of Mathematics. Secondary sources of the research comprise writings on Wittgenstein and his propositions. They are supported by writings on logic, mathematics, language, and epistemology. The research is a qualitative descriptive research. Data are analyzed using descriptive method in which historical, interpretative, analytical, hermeneutic, comparative, deductive, inductive, and heuristic elements are incorporated. According to Witgeinstein, mathematics is a series of language game and techniques of calculation. The foundations of mathematics are knowledge of language, agreements, and rules. Epistemologically, mathematics is a human invention as well as a social construction. Its truth is relative, depending upon the agreement between mathematicians. Mathematics is a logical method and a means to reveal problems of the real world. The development of mathematics needs to be secured by rules of logic